Don't Downplay "Play": Reasons Why Health Systems Should Protect Childhood Play. Issue 5 (24th July 2021) - Nielsen, Lasse
Abstract: Much research has studied the importance of play for children's development. However, questions of its political importance and our public institutions' duties to protect it have been largely neglected. This article argues that childhood play is politically important due to having both intrinsic and instrumental value, and it suggests that the duty to protect the capability for play in childhood falls especially on the public health system. If this argument succeeds, it follows that we have stronger duties toward our children than we currently believe.